2010
DOI: 10.1093/rpd/ncq082
|View full text |Cite
|
Sign up to set email alerts
|

A phantom study showing the importance of compression in conventional diagnostic X-ray examinations

Abstract: Compression was earlier an important and well-managed part of the clinical routine, but during the past 15-20 y the use has diminished, except for mammography, where it is a prerequisite for having images of high quality and low radiation dose. According to national and European regulations and recommendations, it is important to apply the compression technique to obtain the optimal image quality and radiation dose in common conventional diagnostic examinations. Current experience of compression technique is, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 1 publication
0
20
0
Order By: Relevance
“…We performed a median of 10 measurements with an intercostal approach, in liver segments VII/VIII, at depths of 3À5 cm beneath the liver capsule (Dietrich et al 2017;Ferraioli et al 2015). It is known from X-ray examinations that compression reduces attenuation and increases image quality (Olsson et al 2010;Piippo-Huotari et al 2018;Rubin et al 1979). Proximity to the liver capsule is a key factor in securing reliable SWE results, as ultrasound waves in subcutaneous fat attenuate differently (Mast et al 1999), measurement depth affects SWE result reliability (Zhao et al 2011), and ARFIs attenuate more rapidly in subcutaneous fat than in other tissues (Barr et al 2016;Barry et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We performed a median of 10 measurements with an intercostal approach, in liver segments VII/VIII, at depths of 3À5 cm beneath the liver capsule (Dietrich et al 2017;Ferraioli et al 2015). It is known from X-ray examinations that compression reduces attenuation and increases image quality (Olsson et al 2010;Piippo-Huotari et al 2018;Rubin et al 1979). Proximity to the liver capsule is a key factor in securing reliable SWE results, as ultrasound waves in subcutaneous fat attenuate differently (Mast et al 1999), measurement depth affects SWE result reliability (Zhao et al 2011), and ARFIs attenuate more rapidly in subcutaneous fat than in other tissues (Barr et al 2016;Barry et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Prone compression is most frequently used, because it is simple. However, previous research has identified that it is not as effective as compression in the supine position (Piippo‐Huotari, Norrman, Anderzén‐Carlsson & Geijer, ; Olsson et al, ) and not all examinations can be done with the patient in the prone position. For thin patients, it has been shown that there is no compression at all in the prone position (Olsson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, previous research has identified that it is not as effective as compression in the supine position (Piippo‐Huotari, Norrman, Anderzén‐Carlsson & Geijer, ; Olsson et al, ) and not all examinations can be done with the patient in the prone position. For thin patients, it has been shown that there is no compression at all in the prone position (Olsson et al, ). Despite benefits, compression can be experienced as painful and anxiety provoking and one study identified that reduced compression during digital breast tomosynthesis decreased both pain and anxiety, with maintained image quality (Abdullah Suhaimi, Mohamed, Ahmad, & Chelliah, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction of radiation doses and better image quality requires radiographers to use optimized methods such as compression (6,7). The image quality improves with compression because soft tissue is displaced sideways, a thinner body part requires less exposure, and scattered radiation is decreased (7). reduced in recent years in conventional X-ray examinations (3,(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%